Penataan Sistem Penerangan di Pura Beji Desa Les Kecamatan Tejakula, Buleleng - Gunantara, N.; Hartati, R. S.; Dharma, A.; Wijaya, I. K.; Sukerayasa, W.; Mataram, I M.; Pemayun, A. A. G. M.; Sudiarta, I K. P. (Buletin Udayana Mengabdi, 2016)
Beji Temple in Les Village owned by the residents of the Les Village. It is bounded by the east and south by page of Desa Temple / Bale Agung, the west by a vacant lot owned by the village, and the north by Place Baths (Shower). Beji Temple in Les Village has undergone a total refurbishment. With the restoration of the temple in the rebuilding of Beji expanded westward with consideration extant village lands and population growth. Currently Beji Temple has been completely rebuilt and inaugurated by the Village People. In the development process has been carried out the design and implementation of lighting systems. Design lighting system has been designed and a new implementation at the stage of planting cabling that will be used in lighting systems. The design and implementation of the illumination system is designed to provide safety and comfort to the citizens who wishes to engage in worship at night. Besides, it also sheds light on the baths (shower) and contain aesthetic value. Beji Temple lighting system is expected to citizens of Les Village imitate and implement in other temples.
Keywords: Beji Temple, Les Village, design, implementation, lighting system.